A Comparison Between Recombinant Listeria GAPDH Proteins and GAPDH Encoding mRNA Conjugated to Lipids as Cross-Reactive Vaccines for Listeria, Mycobacterium, and Streptococcus - Teran-Navarro, Hector; Salcines-Cuevas, David; Calderon-Gonzalez, Ricardo; Tobes, Raquel; Calvo-Montes, Jorge; Pérez-Del Molino Bernal, Inmaculada Concepción; Yañez-Diaz, Sonsoles; Fresno, Manuel; Alvarez-Dominguez, Carmen (Frontiers in Immunology, 2021)
Cross-reactive vaccines recognize common molecular patterns in pathogens and are able to confer broad spectrum protection against different infections. Antigens common to pathogenic bacteria that induce broad immune responses, such as the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) of the genera Listeria, Mycobacterium or Streptococcus, whose sequences presented more than 95% homology at the N-terminal GAPDH1-22 peptide, are putative candidates for universal vaccines. Here, we explore vaccine formulations based on dendritic cells (DC) loaded with two molecular forms of Listeria monocytogenes GAPDH (LM-GAPDH) such as mRNA carriers or recombinant proteins and compare them with same molecular forms of three other antigens used in experimental vaccines, listeriolysin O of Listeria monocytogenes, Ag85A of Mycobacterium marinum and pneumolysin of Streptococcus pneumoniae. DC loaded with LM-GAPDH recombinant proteins proved to be the safest and most immunogenic vaccine vectors, followed by mRNA encoding LM-GAPDH conjugated to lipid carriers. In addition, macrophages lacked sufficient safety as vaccines for all LM-GAPDH molecular forms. The ability of DC loaded with LM-GAPDH recombinant proteins to induce non-specific DC activation explained their adjuvant potency and their capacity to trigger strong CD4+ and CD8+ T cell responses explained their high immunogenicity. Moreover, their capacity to confer protection in vaccinated mice against challenges with Listeria monocytogenes, Mycobacterium marinum or Streptococcus pneumoniae, validated their efficiency as cross-reactive vaccines. Cross-protection appears to involve the induction of high percentages of GAPDH1-22 specific CD4+ and CD8+ T cells stained for intracellular IFN-g and significant levels of peptide-specific antibodies in vaccinated mice. We concluded that DC vaccines loaded with Listeria monocytogenes GAPDH recombinant proteins are cross-reactive vaccines that seem valuable tools for adult vaccination against Listeria, Mycobacterium and Streptococcus taxonomic groups.